Running the maze - Coughlin, Jack, 1966- (Coughlin, Jack, 1966- Sniper novel., 2012)
Marine Gunnery Sergeant Kyle Swanson is sent into Pakistan, where an international team of medical workers has been executed in order to cover up a deadly terrorist secret.